Evaluating Preceptors. Issue 3 (May 2015) - Bradley, Heather; Cantrell, Donita; Dollahan, Katherine; Hall, Brittany; Lewis, Preston; Merritt, Sharon; Mills, Linda; Moe, Krista; White, Dolores
<x xml:space="preserve">Abstract</x> The purpose of this study was to develop and test the Baptist Health Lexington Performance and Proficiency Assessment for validity and reliability. Twelve expert nurse educators evaluated the instrument for content validity. The sample for test–retest included nurse administrators (5), preceptors (9), and new graduates (10). To evaluate internal consistency, administrators (12), preceptors (66), and new graduates (43) responded. Strong validity and reliability were found for all subscales on the preceptor and new graduate versions.